Co adsoption in kaolinite - Eliel Silva Souza; Paulo Sergio Cardoso Silva (Brazilian Journal of Radiation Sciences)
Adsorption of metal ions in clay minerals has been used as an alternative to water and effluents treatment. Kaolinite is a clay mineral that presents low specific surface area and exchange ion capacity. Nevertheless, structural modifications can be achieved by means of acid or thermal activation. In this paper, it was studied the surface area of kaolinite/bentonite, kaolinite/activated carbon mixtures, thermal activated kaolinite and thermal activated kaolinite/activated carbon mixture. The mixture of kaolinite/activated carbon was tested for pH, contact time, interfering ions and initial concentration effects in the cobalt adsorption. Results showed that the optimized parameters are pH 6 and contact time of 30 min. Chromium acted as a competitive ion, zinc does not appear to have affected adsorption while iron seems to have favored it. Langmuir and Freundlich isotherms indicated that the adsorption of Co in the mixture of kaolinite/activated carbon is a spontaneous process.